2005
DOI: 10.7773/cm.v31i2.59
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity on the growth and biochemical composition of the cyanobacterium Synechococcus sp.

Abstract: The study of cyanobacteria isolated from hypersaline environments is of interest because of their metabolic and ecophysiologic versatility in adapting to extreme conditions of salinity, temperature, irradiance and nutrient availability. The effect of salinity at 0‰, 35‰, 70‰ and 100‰ on the growth, dry weight, and pigment, protein, carbohydrate and lipid production of the cyanobacterium Synechococcus sp. was determined. Bioassays were kept in ALGAL medium equivalent to 8 mM NaNO3, constant aeration, 12:12 h ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…The enhanced respiration indicates that the response ta salin ity stress is an energy consuming process (Zeng and Vonshak, 1998) but the mechanisms have not yet been elucidated. It is probable that salinity stress affects light utilization and metabolism (particularly carbohydrates involved in osmoreg ulation) ta counteract ionic and osmotic stresses (Kebede, 1997;Rosales et al, 2005). Sorne authors have reported an increase in growth with salinity (Dhiab et al, 2007) but they measured Arthrospira growth by following the chlorophyll con tent, which was not the case in our study.…”
Section: ±1 43±1 38±1 16±2mentioning
confidence: 52%
See 1 more Smart Citation
“…The enhanced respiration indicates that the response ta salin ity stress is an energy consuming process (Zeng and Vonshak, 1998) but the mechanisms have not yet been elucidated. It is probable that salinity stress affects light utilization and metabolism (particularly carbohydrates involved in osmoreg ulation) ta counteract ionic and osmotic stresses (Kebede, 1997;Rosales et al, 2005). Sorne authors have reported an increase in growth with salinity (Dhiab et al, 2007) but they measured Arthrospira growth by following the chlorophyll con tent, which was not the case in our study.…”
Section: ±1 43±1 38±1 16±2mentioning
confidence: 52%
“…The decrease in growth with increasing salinity has fre quently been reported in the literature (Rosales et al, 2005;Vonshak et al, 1988;Zeng and Vonshak, 1998;Kebede, 1997). It is accompanied by a decrease in photosynthetic effi.ciency, phycobilin/Chla ratio and PSII activity and an increase in car bohydrate metabolism (Vonshak et al, 1988;Warr et al, 1985).…”
Section: ±1 43±1 38±1 16±2mentioning
confidence: 65%
“…For example, Olvera -Ramirez et al (2000) reported the fatty acid content in Calothrix sp., isolated from a rice field in Mexico, was influenced by the nitrate content in the culture medium and its polyunsaturated fatty acid content was more. The effect of light, temperature and salinity on the lipid and fatty acid composition in some species isolated from different habitats have also been reported by many workers (Rezanka et al, 2003;Maslova et al, 2004;Liu et al, 2005;Rosales et al, 2005). Besides, lipids and fatty acids play an important role in the tolerance of cyanobacterial cells to various environmental stresses such as desiccation, salt induced damage, low temperature, high light induced photoinhibition (Singh et al, 2002).…”
Section: Fatty Acidsmentioning
confidence: 75%
“…Cyanobacteria contain a variety of amino acids and hormonal substances along with sugars and are involved in the improvement of soil texture by acting as chelating agents for heavy metals; they may stimulate the growth of heterotrophic bacteria and also act as growth promoting substances for the plants (Misra and Kaushik, 1989). The biochemical constituents of cyanobacteria depends on the nature of strains, physiological state of the culture and the environment (Vargas et al, 1998;Subhashini et al, 2003;Maslova et al, 2004;Rosales et al, 2005). Subhashini et al (2003) observed significant variations in protein content among the four isolates of Anabaena azollae.…”
Section: Carbohydrate Protein Amino Acids and Lipidsmentioning
confidence: 99%
See 1 more Smart Citation